2021
DOI: 10.3390/jpm11090905
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen as a Master Regulator of Human Pluripotent Stem Cell Function and Metabolism

Abstract: Human-induced pluripotent stem cells (hiPSCs) offer numerous possibilities in science and medicine, particularly when combined with precise genome editing methods. hiPSCs are artificially generated equivalents of human embryonic stem cells (hESCs), which possess an unlimited ability to self-renew and the potential to differentiate into any cell type of the human body. Importantly, generating patient-specific hiPSCs enables personalized drug testing or autologous cell therapy upon differentiation into a desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 140 publications
0
13
0
Order By: Relevance
“…This study also showed the correlation between the cellular metabolism and the maintenance of pluripotency. The lactate production rate was higher, indicating the anaerobic metabolism to meet the energy requirements, in turn upregulating NANOG expression, mainly in 5% O 2 [35]. E-cad/N-cad confirmed the exit from pluripotency.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This study also showed the correlation between the cellular metabolism and the maintenance of pluripotency. The lactate production rate was higher, indicating the anaerobic metabolism to meet the energy requirements, in turn upregulating NANOG expression, mainly in 5% O 2 [35]. E-cad/N-cad confirmed the exit from pluripotency.…”
Section: Discussionmentioning
confidence: 88%
“…2022, 23, x FOR PEER REVIEW 6 of 14 higher in the case of 5% O2. The shift from epithelial to mesenchymal cells is crucial in cell fate decisions and aids in the dynamics of cell differentiation [35]. Furthermore, the epithelial-mesenchymal transition was observed by staining with E-cadherin and N-cadherin (Figure 4C), and the gene expression of E-cadherin and Ncadherin in different oxygen levels aligned with 5% O 2 and 10% O 2 , respectively (Figure 4D).…”
Section: Exit From Pluripotencymentioning
confidence: 89%
See 2 more Smart Citations
“…Developmental biology research shows that, during embryonic development, the entire vascular system has not yet been formed and cannot provide adequate oxygen supply (Nit et al., 2021). The combined data in this study highlight the benefits of culture at reduced oxygen tension for amplifying hiPSC‐VSMCs, enhancing ECM deposition capacity for further vascular tissue engineering development.…”
Section: Discussionmentioning
confidence: 99%